C-Reactive Protein Levels of Sepsis Patients: A Comparison of Three Immunoassay Methods - Devi Rahmadhona; Aryati Aryati; Hardiono Hardiono (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
Quick Sequential Organ Failure Assessment (qSOFA) is a modification of the SOFA score that replaces the Systemic Inflammatory Response Syndrome (SIRS) criteria for sepsis diagnosis. C-reactive protein (CRP) is a marker to help diagnose sepsis. There are not many studies about comparison of CRP level with a variety of instruments and methods, currently. This study aimed to analyze differences in CRP results with particle enhanced turbidimetric immunoassay (PETIA), sandwich immunodetection and reflectometry-immunoassay patients. The study used samples of sepsis patients who were treated in emergency care unit, intensive observation rooms, Intensive Care Unit (ICU) and internal medicine wards of the Dr. Soetomo Hospital Surabaya in May-September 2018. A total of 65 sampels of sepsis patient fulfilled the qSOFA criteria. The CRP examination with the three methods were conducted on all study samples. There were significant differences in CRP levels in the sepsis group using the PETIA and Reflectometry immunoassay methods (p = 0.003), thus both of methods cannot be replace each other. There was no significant difference between CRP levels with PETIA and Sandwich Immunodetection (p=0.172) as well as Reflectometry immunoassay and Sandwich Immunodetection (p=0.251). The selection of instruments and methods for CRP examination is adjusted to laboratory needs and facilities.